Melanomas vs. nevi in high‐risk patients under long‐term monitoring with digital dermatoscopy: do melanomas and nevi already differ at baseline?. (10th January 2017) - Tschandl, P.; Hofmann, L.; Fink, C.; Kittler, H.; Haenssle, H. A.
Abstract: Background: What lesions to select for a most efficient dermatoscopic monitoring of patients with multiple nevi remains an unresolved issue. Objective: To compare the grade of atypia of melanomas and nevi of the same patient at baseline. Methods: Prospective observational study using 236 dermatoscopic baseline images (59 quartets from 59 patients, each including one melanoma detected during follow‐up and three nevi). Dermatologists ( n = 26) were asked to assess the 'grade of dermatoscopic atypia' on a numerical scale and to identify the melanomas. Results: On average, each dermatologist identified 24 of 59 melanomas (40%, range: 11–37). The number of correct picks was greater for dermatologists with moderate (mean: 28) or high (mean: 28) experience compared to beginners (mean 17; P < 0.001). In three of the 59 sets, none of the 26 dermatologists identified the melanoma. The mean grade of dermatoscopic atypia was 2.5 for nevi (95% CI: 2.4–2.6) and 3.0 for melanomas (95% CI: 2.9–3.1, P < 0.001). Limitations: Rating dermatologists were informed that each quartet of images included one melanoma creating substantial deviation from a real‐life situation. Conclusion: A significant proportion of melanomas detected during follow‐up cannot be differentiated from nevi at baseline. This necessitates the additional inclusion of less atypical lesions for monitoring.